The hatmakers - Merchant, Tamzin (Norton Young Readers, 2021)
Cordelia Hatmaker is devastated like the rest of her family when her father disappears while on an expedition to find magical ingredients, but unlike the rest she never loses faith that he will one day be found again. Her aunt and uncle, though grief-stricken, must continue to make the magical Peace Hat for the king to deliver it on time--but when the king's magical clothing from the Hatmaker, Cloakmaker, Watchmaker, Bootmaker, and Glovemaker finally arrive, the objects' enchantments conflict and instead of peace cause unprovoked rage and chaos. War looms on the horizon, and Cordelia is the only one who can find out why the Makers' creations are being twisted to evil.